«ANTISOCIAL DEALS» IN THE LEGISLATION OF FOREIGN STATES - A. V. Kamenshchikov (Russian Journal of Economics and Law)
The article presents a brief analysis of implementation of norms on antisocial deals in the most developed foreign nomocracies. As the issue of the Russian Civil Code reforming is topical nowadays, the described experience of implementation of norms on antisocial deals in a number of foreign countries will be useful for the most efficient way of reforming Article 169 of the Russian Civil Code. The analysis proves that, though various countries adhere to the principle of freedom of agreements, but the most developed nomocracies admit an agreement invalid if it contradicts to the morals or public order.